Integration of VSM and SMED for Optimization of the CCB Milling Process - Yusrizal; Heru Darmawan; Rani Rahmadiyani (Jurnal Ragam Pengabdian, 2026)
Productivity improvement in manufacturing systems requires systematic identification and elimination of waste, particularly in bottleneck processes. This study was conducted at PT XYZ, an automotive component manufacturer experiencing low productivity in the CCB part production line. The milling process was identified as the primary bottleneck, with an initial cycle time of 472 seconds for 6 pieces and an average output of 550 pcs/day, achieving only 75.6% of the production target. This research aims to identify the causes of waste, reduce cycle time in the milling process, and increase production output in line with management targets. The study applies Value Stream Mapping (VSM) to analyze material and information flow, Process Activity Mapping (PAM) to classify internal and external activities, and the Single Minute Exchange of Dies (SMED) method to minimize setup time. Improvements were implemented using the PDCA (Plan–Do–Check–Act) cycle. Root cause analysis using fishbone and 5W+1H identified manual clamping operations as the main contributor to excessive internal time and variability. A semi-automatic pneumatic clamping system was introduced to replace manual bolt tightening and clamp handling. The results show a reduction in internal setup activities from 12 to 9 activities and a decrease in cycle time from 472 seconds to 425 seconds (9.9%). Consequently, daily production output increased from 550 pcs/day to 652 pcs/day, representing an 18.5% productivity improvement and exceeding the initial 10% target. The findings confirm that integrating VSM and SMED with semi-automation effectively enhances operational performance without full-scale automation investment.